Post- traumatic stress, anxiety and perceived stress - Liabre, Maria M.; Hadi, Fawziah (Beirut Lebanese Association for Educational Sciences; Kuwait Society for the advancement of Arab, 2008)
In this chapter, the results of the study shows that a significant number of children and young people are experiencing symptoms of psychological distress that have the potential for interfering with their development and, if left untreated, place them at risk for serious problems as adults.
: Chapter in a Book
Keywords: Guerre; Psychological Health; Santé psychologique; War